Genetic analysis of resistance to gray leaf spot of midaltitude maize inbred lines - Menkir, A.; Ayodele, M. (Wiley, 2005)
Gray leaf spot (GLS), caused by Cercospora zeae-maydis Tehon & E.Y. Daniels, poses a serious threat to maize (Zea mays L.) production in sub-Saharan Africa. The knowledge of inheritance of resistance to GLS in new inbred lines would be useful for efficient development of hybrids and synthetics. In this study, we determined (i) the mode of inheritance of resistance to GLS in midaltitude inbred lines, (ii) the effect of different doses of resistance to GLS in parents on the levels of resistance of their hybrids, and (iii) heterotic effects for GLS resistance. Ninety-six hybrids from 24 inbreds were produced using the Design II mating scheme. The parents and the hybrids were evaluated in separate trials in five environments in Nigeria. Both general (GCA) and specific (SCA) combining abilities were significant (P < 0.001), with GCA accounting for >70% of the variation for GLS scores, days to silking, plant height, ear height, ear aspect, and ear rot; 68% for grain yield; and 60% for plant aspect (visual phenotypic appeal) score. Predominantly, additive genetic effects influenced resistance to GLS and other traits in maize hybrids. Most of the crosses with one or more resistant parents produced resistant hybrids, whereas most crosses between susceptible lines generated susceptible hybrids. Prediction of GLS in hybrids using midparent values resulted in a R 2 value of 0.53 for GLS disease score recorded 38 d after midsilking (GLS Score2). Negative heterosis observed in 75 hybrids for GLS Score2 suggested that resistance to GLS could be improved in midaltitude hybrids.